(untitled) (Agroindustrial Science, 2024)
Craft beer is of vital importance because it is brewed with natural ingredients and has been known worldwide for its variety of flavour and excellent quality since ancient times. Therefore, the aim of this research work was to brew craft beer with the inclusion of corn, pineapple pulp (A. comosus) and coconut essence (C. nucifera) and its evaluation of technological and sensory properties. An A*B+1 factorial design was used, in which cereal mixtures (barley and maize) and flavour mixtures (pineapple pulp and coconut essence) were evaluated. The results showed a significant difference (p < 0.05) between the means of the treatments, determining that GT1 (75% barley + 25% maize + 2.5% pineapple pulp + 1% coconut essence), presented similar values to the control treatment with a total acidity of 0.20%; alcohol content of 4.95% and a colour by spectrophotometry of 7.05 SRM. In addition, it presented the best sensory profiles, according to the categories evaluated, with a mild aroma; moderate bitter taste; golden colouring characteristic of the sample and a higher level of acceptability. It is necessary to mention that the use of new raw materials, such as maize, of which only 20% is used in Ecuador for the food industry, by including it in the formulation of beers, increases the production and consumption of this grain, thus promoting new alternatives that contribute to the country’s socio-economic sector.